Independent development of the Reach and the Grasp in spontaneous self-touching by human infants in the first 6 months - Thomas, Brittany L.; Karl, Jenni M.; Whishaw, Ian Q. (Frontiers in Psychology, 2015)
The Dual Visuomotor Channel Theory proposes that visually guided reaching is a composite of two movements, a Reach that advances the hand to contact the target and a Grasp that shapes the digits for target purchase. The theory is supported by biometric analyses of adult reaching, evolutionary contrasts, and differential developmental patterns for the Reach and the Grasp in visually guided reaching in human infants. The present ethological study asked whether there is evidence for a dissociated development for the Reach and the Grasp in nonvisual hand use in very early infancy. The study documents a rich array of spontaneous self-touching behavior in infants during the first 6 months of life and subjected the Reach movements to an analysis in relation to body target, contact type, and Grasp. Video recordings were made of resting alert infants biweekly from birth to 6 months. In younger infants, self-touching targets included the head and trunk. As infants aged, targets became more caudal and included the hips, then legs, and eventually the feet. In younger infants hand contact was mainly made with the dorsum of the hand, but as infants aged, contacts included palmar contacts and eventually grasp and manipulation contacts with the body and clothes. The relative incidence of caudal contacts and palmar contacts increased concurrently and were significantly correlated throughout the period of study. Developmental increases in self-grasping contacts occurred a few weeks after the increase in caudal and palmar contacts. The behavioral and temporal pattern of these spontaneous self-touching movements suggest that the Reach, in which the hand extends to make a palmar self-contact, and the Grasp, in which the digits close and make manipulatory movements, have partially independent developmental profiles. The results additionally suggest that self-touching behavior is an important developmental phase that allows the coordination of the Reach and the Grasp prior to and concurrent with their use under visual guidance.